Common controversies in total knee replacement surgery: Current evidence. - Nikolaou, Vasileios S; Chytas, Dimitrios; Babis, George C (World J Orthop, 2014)
Total knee replacement (TKR) is a widely used operation that has radically improved the quality of life of millions of people during the last few decades. However, some technical details, concerning the surgical procedure and the rehabilitation following total knee arthroplasty, are still a matter of a strong debate. In this review of the literature, we have included the best evidence available of the last decade, in an effort to shed light on some of the most controversial subjects related to TKR surgery. Posterior-stabilized or cruciate-retaining prosthesis? To use a tourniquet during operation or not? Do patients need continuous passive motion for their post-surgery rehabilitation? To resurface patella or not? These are some of the most controversial topics that until now have been persistent dilemmas for the orthopedic surgeon. Results of this systematic review of the literature are highly controversial. These conflicting results are an indication that larger and more well conducted high quality trials are needed in order to gain more secure answers. At the same time, it is becoming apparent that a meticulous operative technique, respecting the soft tissue envelope and knowing the principles of alignment and soft tissue balancing, are some of the parameters that might contribute more to achieving the optimal results for the patients.